DISTURBED LEFT ATRIAL CONDUIT FUNCTION IN HYPERTENSIVE PATIENTS. (April 2021) - Georgieva, Neli; Borizanova-Petkova, Angelina; Krastev, Bozhidar; Poroyliev, Nikolay; Kinova, Elena; Goudev, Assen
Abstract: Objective: Arterial stiffness is an independent risk factor in arterial hypertension, but little is known about the association between left atrial remodeling and arterial stiffness in middle – aged hypertensive patients. AIM: To investigate the early changes in left atrial (LA) mechanical function and parameters of arterial stiffness in a population of asymptomatic hypertensive individuals. Design and method: A total 95 patients (57 ± 14 years) with hypertension, were separated in two groups: 22 patients with normal EA/Ees ratio (Arterial elastance (AE) and ventricular elastance (Ees))and 73 hypertensive patients with decrease EA/Ees ratio, marker for ventriculo – arterial coupling (VAC). All patients underwent standard two - dimentional echocardiography with Speckle tracking analysis for LA – reservoir (LARs), conduit (LAScd) and contractile (LASct) strain. End – systolic pressure was determined from the brachial pulse wave. Arterial elastance (AE) and ventricular elastance (Ees) were calculated as and – systolic pressure/stroke volume and end – systolic pressure/end – systolic volume. Parameters for arterial stiffness – 24 - hour central systolic pressure (cSys24 h) and central pulse pressure (cPP24 h) were measured non – invasively with oscillometric method by Mobil-O-graph PWA. Results: RESULTS: Statistically significant differences in parameters of vascular stiffness were found in patients with normal VAC in comparison with disturbed EA/Ees: cSys24 h (107.64 ± 9.19 vs. 116.64 ± 16.7 mm Hg, p = 0.02), cPP24 h (40.23 ± 11.84 vs. 48.08 ± 10.51 mm Hg, p = 0.04). There were statistically significant differences in echocardiography parameters between patients with disturbed VAC in comparison to other group: LAScd (16.86 ± 1.94 vs. 19.49 ± 1.35 %, p < 0.001), LASr (30.22 ± 3.26 vs. 31.81 ± 5.32 %, p = 0.007) and LAVI (30.95 ± 9.22 vs. 36.65 ± 8.83 ml/m 2, p = 0.007). There was positive correlation between LAScd with EA/Ees (r = 0.272, p < 0.008) and negative E/Em (r = -0.264, p < 0.01). LAVI correlated moderate positively with E/Em ratio (r = 0.407, p < 0.0001) and negatively with LAScd (r = - 0.410, p < 0.0001). Conclusions: LA mechanical deformation is dependent to arterial stiffness. Reduced LAScd could play a key role in early stages of atrial remodeling. These findings could be used for the prediction of cardiovascular events in this population.